2016
DOI: 10.3109/00952990.2016.1149591
|View full text |Cite
|
Sign up to set email alerts
|

Text2Quit: an analysis of participant engagement in the mobile smoking cessation program

Abstract: Using interactive tools such as pledges and reporting on smoking status were predictive of cessation. Further study of program features is required to understand how to optimally design text messaging programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
24
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 21 publications
4
24
3
Order By: Relevance
“…Engagement, for instance, has been conceptualized in previous studies both as the usage or the subjective experience with the program [ 14 ]. For texting-based programs, there is some evidence that the predominant engagers are female [ 15 ] and older and that they exhibit lower rates of daily cigarette consumption [ 16 ], but none of these studies were conducted on adolescents.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Engagement, for instance, has been conceptualized in previous studies both as the usage or the subjective experience with the program [ 14 ]. For texting-based programs, there is some evidence that the predominant engagers are female [ 15 ] and older and that they exhibit lower rates of daily cigarette consumption [ 16 ], but none of these studies were conducted on adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Participants who elected to stop the program were less likely to be abstinent at follow-up. In another study by Heminger et al [ 15 ], rather than overall engagement, postquit engagement and the use of specific program features such as pledges were specifically predictive of 6-month abstinence. Even more accurately, a study by Christofferson et al [ 16 ] identified five different classes of user engagement, which in turn were associated with different levels of interventional success.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations